Microsurgical Reconstruction of the Lower Extremity - Pederson, William C.; Grome, Luke (Seminars in Plastic Surgery, 2019)
Reconstruction of bony and soft tissue defects of the lower extremity has been revolutionized by the advent of microsurgical tissue transfer. There are numerous options for reconstruction. Possibilities include transfer of soft tissue, composite (bone and soft tissue) tissue, and functional muscle. Many lower extremity reconstructions require staged procedures. Planning is of paramount importance especially in regard to vascular access when multiple free flaps are required. Soft tissue reconstruction of the lower extremity may be accomplished with muscle flaps such as the rectus femoris and latissimus dorsi covered with a skin graft. Fasciocutaneous flaps such as the anterolateral thigh flap may be more appropriate in a staged reconstruction which requires later elevation of the flap. Loss of a significant portion of bone, such as the tibia, can be difficult to manage. Any gap greater than 6 cm is considered a reasonable indication for vascularized bone transfer. The contralateral free fibula is the donor site of choice. Functional reconstruction of the anterior compartment of the leg may be performed with a gracilis muscle transfer, effectively eliminating foot drop and providing soft tissue coverage. Muscle tensioning is critical for effective excursion and dorsiflexion of the foot. Long-term results of microsurgical reconstruction of the lower extremity show good results and reasonable rates of limb salvage.
Keywords: lower extremity reconstruction; microsurgery; functional muscle transfer; free fibula; trauma